THE IMPACT OF ONLINE COLLABORATIVE LEARNING ON STUDENTS’ PROCEDURAL WRITING SKILLS IN EFL CLASSROOM - Fitriadi Lubis (Mandalika Institute, 2025)
This study explores the impact of Online Collaborative Learning (OCL) on EFL students’ procedural writing skills through a qualitative literature review. Given the increasing use of digital tools in education, especially in the context of the COVID-19 pandemic, this research investigates how OCL fosters collaboration, peer feedback, and critical thinking, all of which contribute to the development of students’ writing abilities. A comprehensive review of 10 relevant studies reveals that OCL significantly enhances students’ procedural writing by promoting interaction among peers, providing real-time feedback, and offering flexible learning environments. The literature suggests that peer feedback, facilitated through both synchronous and asynchronous online platforms, plays a vital role in improving the clarity, structure, and precision of procedural texts. However, challenges related to unequal participation in asynchronous settings are noted, highlighting the need for careful management of collaborative tasks. The findings align with Vygotsky’s sociocultural theory, which emphasizes the importance of social interaction in cognitive development. This review contributes to a deeper understanding of the potential benefits and limitations of OCL in improving writing skills, particularly in the procedural writing genre. The study concludes with recommendations for future research, including exploring the long-term impact of OCL on writing skills and investigating strategies to improve student engagement in collaborative environments.